AAC Tundra great northern dry bean - Balasubramanian, P. M.; Mündel, H.-H.; Conner, R. L.; Hou, A. (Canadian Journal of Plant Science, 2012)
Balasubramanian, P. M., Mündel, H.-H., Conner, R. L. and Hou, A. 2012. AAC Tundra great northern dry bean. Can. J. Plant Sci. 92: 1403–1405. AAC Tundra is a high-yielding, early-maturing great northern bean (Phaseolus vulgaris L.) with an upright, indeterminate bush growth habit with long vines (Type IIb). AAC Tundra was developed at the Agriculture and Agri-Food Canada (AAFC) Research Centre, Lethbridge, AB. AAC Tundra has a large seed size and improved field resistance to white mould compared with the check cultivar AC Polaris. AAC Tundra is suitable for irrigated wide row production in Alberta and Saskatchewan.